Aplikasi “GIZIe” Untuk Mengetahui Status Gizi Balita Menggunakan Metode Forward Chaining - Fiby Nur Afiana; Ika Romadoni Yunita (Ikatan Ahli Informatika Indonesia (IAII), 2019)
Based on the results of Nutritional Status Monitoring (PSG) conducted by the Ministry of Health in several regions in Indonesia there are sufferers of malnutrition from the age of 0 - 59 months. Banyumas Regency itself entered into the red zone the highest number of cases of malnutrition with 65 cases. For the Baturraden area with an area of ​​45.35 km2 and having 12 villages, there is a Puskesmas which only has 1 general practitioner, 3 nurses, 6 midwives and 1 nutritionist. Based on the Recaputulation of the Agency for Health and Human Resource Development, the Health Center I Baturraden is considered still not meeting the standard number of Health Human Resources. In addition, the lack of public awareness and economic reasons further worsened the condition of community nutrition. Seeing the cases that occur requires a system that can diagnose early conditions of malnutrition in children that can be accessed directly by everyone by utilizing expert system information technology. The purpose of this study is to design and build a mobile phone (android) application called ‘Gizie’ by using the forward chaining method for Puskesamas 1 Baturraden Banyumas Regency which can help medical personnel and parents diagnose early malnutrition in children. The research method used is the research and development method (R & D) to produce certain products, and test the effectiveness of these products.